The Etymology of Latin nimbus (and its Iranian Cognates) - Cohen, Paul S. (Collectanea Philologica, 2020)
After a brief review of prior etymological attempts found in the literature, a complete, rule-governed etymology of Latin nimbus ‘rain cloud, sudden downpour, etc.’ – including a precise explanation of the medial nasal – is propounded. It is based on the Indo-European reduplication process that produces nouns, as delineated by Cohen (2014; 2015; 2017), and on Latin sound laws given and exemplified by Weiss (2009).